Acute exacerbation in chronic bird fancier's lung with pleuroparenchymal fibroelastosis. Issue 1 (20th November 2020) - Sugino, Keishi; Ono, Hirotaka; Watanabe, Natsumi; Igarashi, Seiji; Hebisawa, Akira; Tsuboi, Eiyasu
Abstract: A 71‐year‐old non‐smoker woman was admitted to our hospital complaining of a six‐month history of dry cough. She had kept java sparrow for nine years and has been raising budgerigars for the previous eight months. High‐resolution computed tomography (HRCT) images of the chest revealed reticulonodular lesions predominantly in the bilateral upper lobes. Surgical lung biopsy specimens showed non‐caseous epithelioid cell granulomas in the alveolar spaces, including irregular and centrilobular fibrosis with pleuroparenchymal fibroelastosis. When she started using a duck feather duvet at home, she developed dyspnoea and chest HRCT abnormalities progressively deteriorated. The results of precipitation of antibodies against duck feather, java sparrow, and budgerigars dropping extracts were positive in sera. Consequently, the patient was diagnosed as having chronic bird fancier's lung with acute exacerbation caused by the use of a feather duvet. After combination treatments with corticosteroid and cyclosporine, her respiratory symptoms and reticulonodular shadow immediately improved. Abstract : This is a case of chronic bird fancier's lung (BFL) (java sparrow and budgerigars) presenting with acute exacerbation due to exposure to feather duvet. Chronic BFL occasionally can associate with pleuroparenchymal fibroelastosis (PPFE). Searching for precipitins against antigens of bird droppings and feather is useful for our clinicians to make a diagnosis of BFL.